Ultrasound-Triggered Release of 5-Fluorouracil from Soy Lecithin Echogenic Liposomes - Charles Izuchukwu Ezekiel; Alain Murhimalika Bapolisi; Roderick Bryan Walker; Rui Werner Maçedo Krause (MDPI AG, 2021)
Colorectal cancer is the third most diagnosed cancer and the second leading cause of death. The use of 5-fluorouracil (5-FU) has been the major chemotherapeutic treatment for colorectal cancer patients. However, the efficacy of 5-FU is limited by drug resistance, and bone marrow toxicity through high-level expression of thymidylate synthase, justifying the need for improvement of the therapeutic index. In this study, the effects of ultrasound on echogenic 5-FU encapsulated crude soy liposomes were investigated for their potential to address these challenges. Liposomes were prepared by thin-film hydration using crude soy lecithin and cholesterol. Argon gas was entrapped in the liposomes for sonosensitivity (that is, responsiveness to ultrasound). The nanoparticles were characterized for particle size and morphology. The physicochemical properties were also evaluated using differential scanning calorimetry, Fourier transform infrared and X-ray diffraction. The release profile of 5-FU was assessed with and without 20 kHz low-frequency ultrasound waves at various amplitudes and exposure times. The result reveal that 5-FU-loaded liposomes were spherical with an encapsulation efficiency of approximately 60%. Approximately 65% of 5-FU was released at the highest amplitude and exposure time was investigated. The results are encouraging for the stimulated and controlled release of 5-FU for the management of colorectal cancer.